Spotlight on Neuroimmunology: Illustrations from Neurodegenerative Diseases - Abdelaziz Ghanemi; Besma Boubertakh (International Journal of Public Health Science (IJPHS), 2017)
The immune system plays key roles in the defense of the organism. However, the effects of the immune system are not limited to the immune functions and have impacts beyond the anti-pathogenes role. Indeed, neuroimmunology is a representative field of how the immune system affects non-immune biological and physio-pathological functions. Herein, we have selected a number of neurodegenerative diseases as illustrative examples to put a spotlight on this important field. Importantly, clarifying the links and interactions between the immune system and the nervous system represents key elements for the understanding neurodegenerative diseases since it will lead to new theories about the pathogenesis and the mechanisms underlying the related processes and thus, provide us with new data and novel tools to both describe the related pathways and develop new therapeutic approaches as well as diagnostic approaches and research methodologies based on such new discoveries.